Co-registration Analysis of Fluorodopa and Fluorodeoxyglucose Positron Emission Tomography for Differentiating Multiple System Atrophy Parkinsonism Type From Parkinson's Disease - Xian, Wen-biao; Shi, Xin-chong; Luo, Gan-hua; Yi, Chang; Zhang, Xiang-song; Pei, Zhong (Frontiers in Aging Neuroscience, 2021)
It is difficult to differentiate between Parkinson’s disease and multiple system atrophy parkinsonian subtype (MSA-P) because of the overlap of their signs and symptoms. Enormous efforts have been made to develop positron emission tomography (PET) imaging to differentiate these diseases. This study aimed to investigate the co-registration analysis of 18F-fluorodopa and 18F-flurodeoxyglucose PET images to visualize the difference between Parkinson’s disease and MSA-P. We enrolled 29 Parkinson’s disease patients, 28 MSA-P patients, and 10 healthy controls, who underwent both 18F-fluorodopa and 18F-flurodeoxyglucose PET scans. Patients with Parkinson’s disease and MSA-P exhibited reduced bilateral striatal 18F-fluorodopa uptake (p < 0.05, vs. healthy controls). Both regional specific uptake ratio analysis and statistical parametric mapping analysis of 18F-flurodeoxyglucose PET revealed hypometabolism in the bilateral putamen of MSA-P patients, and hypermetabolism in the bilateral putamen of Parkinson’s disease patients. There was a significant positive correlation between 18F-flurodeoxyglucose uptake and 18F-fluorodopa uptake in the contralateral posterior putamen of MSA-P patients (rs = 0.558, p = 0.002). Both 18F-flurodeoxyglucose and 18F-fluorodopa PET images showed that the striatum was rabbit-shaped in the healthy control group segmentation analysis. A defective rabbit-shaped striatum was observed in the 18F-fluorodopa PET image of patients with Parkinson’s disease and MSA-P. In the segmentation analysis of 18F-flurodeoxyglucose PET image, an intact rabbit-shaped striatum was observed in Parkinson’s disease patients, whereas a defective rabbit-shaped striatum was observed in MSA-P patients. These findings suggest that there were significant differences in the co-registration analysis of 18F-flurodeoxyglucose and 18F-fluorodopa PET images, which could be used in the individual analysis to differentiate Parkinson’s disease from MSA-P.